Synthesis and characterization of hole-transport materials in polysiloxane - Jahng, WS; Kim, JK; Park, KH; Kim, N; Lee, CJ (TAYLOR & FRANCIS LTD, 2002)
Triphenylamine(TPA) substituted polysiloxane was synthesized as the hole-transporting material. Field dependence of the hole mobility and photoconductivity were measured using the time-of flight and simple DC photocurrent measurement, respectively. We demonstrated that the film of polysiloxane with pendant TPA units higher hole mobility (3.2 x 10(-5)cm(2)/Vsec at E = 6 x 10(5)) than that of the conventional poly(N-vinylcarbazole) and carbazole substituted polysiloxane. Further experiments are required to test these new materials as hole transporting layers in photorefractive and electroluminescent devices.